Study of Factors Affecting Consumers’ Willingness to Pay for Certified Traceable Pork in Yanbian - Hu, Shuang-Yu; Piao, Shi-Yong; Li, Zhi-Run; Sun, Yu-Cong; Jin, Xuan-You; Lee, Jong-In (Journal of Agriculture & Life Science, 2021)
With the development of the economy and the continuous improvement of people’s living standards, consumers’ increasing demand for safe food has become an inevitable trend of social development. On the one hand, food safety is an urgent social problem needed to be solved in China. On the other hand, the food safety guarantee method based on a traceability system is popular. This paper systematically studies the influencing factors of consumers’ willingness to pay for the extra price of traceable pork in the Yanbian area through empirical analysis. The result showed that consumers’ attitude and subjective norms, and perceived behavior control, have significantly positively affect consumers’ willingness to pay the extra price. Meanwhile, consumers’ perceived risk of traceable pork significantly moderates the effect on consumers’ attitude and willingness to pay an extra price. The results can provide the corresponding reference for government agencies to formulate policies and provide valuable suggestions for enterprises to develop a pork traceability market to realize the development of a pork traceability system in the Yanbian area to ensure consumers’ food safety.